Timing of therapeutic hypothermia and outcomes in neonates with hypoxic-ischemic encephalopathy: A cohort study in a middle-income country - Sergio Agudelo-Pérez; Gloria Troncoso; Lina María Gutiérrez Montenegro; Juliana López Ordoñez (PLoS ONE, 2026)
Background Therapeutic hypothermia improves survival and neurodevelopmental outcomes in neonates with hypoxic-ischemic encephalopathy when initiated within 6 hours of birth. However, in low- and middle-income countries, delays in referral and access to tertiary care often preclude early initiation and the benefits of therapeutic hypothermia beyond the recommended window remain uncertain. We aimed to assess whether initiating therapeutic hypothermia between 6 and 12 hours after birth is associated with a higher risk of mortality and/or brain injury than initiation within 6 hours in neonates with moderate or severe hypoxic-ischemic encephalopathy. Methods We conducted a retrospective cohort study of 173 neonates with moderate or severe hypoxic-ischemic encephalopathy treated with servo-controlled whole-body therapeutic hypothermia at a tertiary care center in Colombia. Neonates were categorized based on the timing of therapeutic hypothermia initiation as ≤6 h or >6–12 h after birth. The primary outcome was a composite of in-hospital mortality and/or brain injury confirmed by magnetic resonance imaging during the first week of life. Multivariate logistic regression was used to adjust for confounding variables. Results Of the 173 neonates, 44.5% received therapeutic hypothermia within 6 hours and 55.5% after 6–12 hours. A composite outcome was observed in 40.6% of the patients. Delayed therapeutic hypothermia was not significantly associated with an increased risk of the composite outcome compared to early initiation (adjusted odds ratio [OR]: 1.83; 95% CI: 0.86–3.90). Seizures and severe hypoxic-ischemic encephalopathy were found to be independent predictors of adverse outcomes. Conclusions In this cohort, initiation of therapeutic hypothermia between 6 and 12 h after birth was not significantly associated with worse neurological or mortality outcomes than initiation within 6 h. These findings suggest that delayed therapeutic hypothermia may still confer benefits in settings where early initiation is challenging, underscoring the need to strengthen referral systems and further investigate the optimal therapeutic window.